2007
DOI: 10.1097/mao.0b013e318067e322
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Caloric Response and Outcome in Patients With Benign Paroxysmal Positional Vertigo

Abstract: Canal paresis is not associated with a lower outcome to repositioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Vestibular hypofunction was reported by other authors in BPPV patients [24][25][26][27] . The Balance Rehabilitation Unit (BRU TM ) posturography showed that the stability limit area values were similar to those in the control group, indicating that our patients with BPPV had stability to move their body mass center and keep balance without changing the support basis.…”
Section: Discussionmentioning
confidence: 54%
“…Vestibular hypofunction was reported by other authors in BPPV patients [24][25][26][27] . The Balance Rehabilitation Unit (BRU TM ) posturography showed that the stability limit area values were similar to those in the control group, indicating that our patients with BPPV had stability to move their body mass center and keep balance without changing the support basis.…”
Section: Discussionmentioning
confidence: 54%
“…Babac considers success for negative DHM also without specifying whether if negative manoeuvre is referred to symptoms or just nystagmus; Oliveira for negative nystagmus regardless of patient‐reported symptoms or positional vertigo on the DHM. Most authors, like Pérez‐Fernández, Pérez and López‐Escámez, consider recovery from an episode when no positional nystagmus or vertigo on the DHM is observed, without taking into account the persistence of symptoms in daily life. In other studies, resolution criteria is not specifically defined, assuming that negativization of nystagmus is used.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, there is not a unanimous definition of episode recovery among authors: recovery is usually defined as the disappearance of nystagmus on the control DHM, but disappearance of vertigo during DHM and changes in general status (GS) in daily life activities reported by patients at follow-up are also important results. Often, resolution criteria are usually not specified or there is no consensus between authors among CSP-PBBV literature [21][22][23][24][25][26][27][28] .…”
mentioning
confidence: 99%
“…Strupp et al [7] have pointed out the reversibility of caloric hypo-excitability in case of LC-BPPV after liberatory maneuver. On the other hand, Molina et al [8] have used caloric testing as a monitoring tool. They have found that 25% of patients with BPPV (16 of 54) had canal paresis at the diagnosis and 16% (9 of 56) still had canal paresis 1 y later.…”
Section: Discussionmentioning
confidence: 99%
“…They have reported that canal paresis was not associated with a lower outcome to repositioning maneuver. It was interesting to observe the normalization of caloric responses over time with the resolution of positional symptoms [8] .…”
Section: Discussionmentioning
confidence: 99%